Influence of ground motion characteristics on the optimal single concave sliding bearing properties for base-isolated structures. Issue 104 (January 2018) - Castaldo, P.; Tubaldi, E.
Abstract: This study examines the influence of ground motion characteristics on the optimal friction properties of single concave sliding bearings employed for the seismic isolation of structural systems. The evaluation of the optimal properties is carried out by considering a non-dimensional formulation which employs the peak ground acceleration (PGA) and the peak ground acceleration-to-velocity (PGA/PGV) ratio as ground motion parameters. A two-degree-of-freedom (2dof) model is employed to describe the isolated system and two different families of records representative respectively of near fault and far field seismic inputs are considered. Following the nondimensionalization of the equation of motion for the proposed ground motion parameters, it is shown that the non-dimensional responses obtained for the two types of seismic inputs are similar. This result confirms that PGA/PGV is a good indicator of the frequency content and of other characteristics of ground motion records, helping to reduce the scatter in the response. Regression expressions are also obtained for the optimal values of the friction coefficient that minimizes the superstructure displacements relative to the base as a function of the abovementioned ground motion parameter and of the dimensionless system parameters. These expressions can be used for the preliminary estimation of the optimal properties of isolation bearings with a single concave sliding surface or double concave sliding surfaces with equal friction coefficient. Highlights: Influence of ground motion parameters on performance of systems isolated by FPS. PGA/PGV assumed as representative of ground motion frequency characteristics. Nondimensionalization of the equations of motion in function of PGA and PGA/PGV. Response to both near-fault and far-field earthquakes is investigated. Regression expressions accounting for effect of PGA/PGV on optimal friction.